1985
DOI: 10.1901/jaba.1985.18-87
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale Reductions in Speeding and Accidents in Canada and Israel: A Behavioral Ecological Perspective

Abstract: We assessed the effects of posted feedback and warning ticket programs on speeding and accidents in two cities. In Experiment 1, speeding feedback signs were effective even when 10 were used in Dartmouth, Nova Scotia, and reductions in speeding were associated with reductions in accidents. The effectiveness of the signs was correlated with the number of intersections and residences within 0.5 km beyond them, and the signs had no effect on untreated streets. In Experiment 2, posted feedback and a warning progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 3 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…This may include the introduction of more speed cameras, which have been found to reduce speeding significantly [74]. Feedback signs which broadcast the percentage of drivers who have stayed within the speed limit of an area have also been found to be effective at reducing speeding and resulting accidents [75].…”
Section: Discussionmentioning
confidence: 99%
“…This may include the introduction of more speed cameras, which have been found to reduce speeding significantly [74]. Feedback signs which broadcast the percentage of drivers who have stayed within the speed limit of an area have also been found to be effective at reducing speeding and resulting accidents [75].…”
Section: Discussionmentioning
confidence: 99%
“…Although few drivers directly experienced the aversive consequence of a fine, many more may have seen police cars patrolling handicapped parking sites and ticketing violators. Van Houten and Nau (1983) and Van Houten et al (1985) indicated that the effectiveness ofpolice enforcement procedures may be a function of the density and visibility of punishment.…”
Section: Social Validity Datamentioning
confidence: 99%
“…Issues have included littering (Geller, Winett, & Everett, 1982), trash packaging (Stokes & Fawcett, 1977), city crime (Schnelle, Kirchner, Casey, Uselton, & McNees, 1977), and speeding (Van Houten & Nau, 1983;Van Houten et al, 1985).…”
mentioning
confidence: 99%
“…Another approach to reducing the number of injuries caused by motor vehide crashes is to change behaviors relevant to the prevention of vehide crashes. Behavior analysis has been applied with some success to affect precursors to vehide crashes, most notably the prevention ofalcohol-impaired driving (e.g., see review by Geller & Lehman, 1989) and speeding (e.g., Van Houten et al, 1985;Van Houten & Van Houten, 1987). However, behavior analysis has been underused in the examination and modification ofnumerous other behaviors relevant to vehide crash avoidance.…”
mentioning
confidence: 99%